1998
DOI: 10.1083/jcb.141.5.1243
|View full text |Cite
|
Sign up to set email alerts
|

Death-effector Filaments: Novel Cytoplasmic Structures that Recruit Caspases and Trigger Apoptosis

Abstract: The death-effector domain (DED) is a critical protein interaction domain that recruits caspases into complexes with members of the TNF-receptor superfamily. Apoptosis can also be induced by expressing certain DED-containing proteins without surface receptor cross-linking. Using Green Fluorescent Protein to examine DED-containing proteins in living cells, we show that these proteins cause apoptosis by forming novel cytoplasmic filaments that recruit and activate pro-caspase zymogens. Formation of these filament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
218
4

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 218 publications
(253 citation statements)
references
References 42 publications
31
218
4
Order By: Relevance
“…3c) showed that HSV-2 R1 co-immunoprecipitated with casp-8 DED-AB GFP (lane 3), but not with casp-8 CD GFP (lane 4) or with FADD YFP (lane 5). Consistent with these results, we also observed that HSV-2 R1 could block the formation of previously-described [30] cytoplasmic filaments in casp-8 DED-AB GFP-expressing cells but not those seen in FADD YFP-expressing cells (Fig. S3).…”
Section: Hsv-2 R1 Impairs Apoptosis Induced By Caspase-8 Over-expressionsupporting
confidence: 91%
See 3 more Smart Citations
“…3c) showed that HSV-2 R1 co-immunoprecipitated with casp-8 DED-AB GFP (lane 3), but not with casp-8 CD GFP (lane 4) or with FADD YFP (lane 5). Consistent with these results, we also observed that HSV-2 R1 could block the formation of previously-described [30] cytoplasmic filaments in casp-8 DED-AB GFP-expressing cells but not those seen in FADD YFP-expressing cells (Fig. S3).…”
Section: Hsv-2 R1 Impairs Apoptosis Induced By Caspase-8 Over-expressionsupporting
confidence: 91%
“…3b). In these adherent cells, fluorescence appeared diffuse throughout the cytoplasm, as reported in conditions where apoptosis induced by casp-8 GFP was inhibited by z-VADfmk [30]. Immunoblotting with anti-GFP antibody showed that casp-8 GFP (*85 kDa) was nearly completely absent in control cells, which accumulated the processed casp-8 p10 GFP product (*42 kDa) (Fig.…”
Section: Hsv-2 R1 Impairs Apoptosis Induced By Caspase-8 Over-expressionsupporting
confidence: 73%
See 2 more Smart Citations
“…Similarly, caspase-10, c-FLIP (Irmler et al 1997) and v-FLIP (Bertin et al 1997;Thome et al 1997) have two DEDs, while caspase-1, -2, -4 and -5 have only one CARD. Interestingly, two repeated DEDs of caspase-8 (Casp8NC-DED) were involved in induction of apoptosis (Siegel et al 1998), while two repeated DEDs of v-FLIP inhibit apoptosis (Bertin et al 1997;Thome et al 1997).…”
Section: Introductionmentioning
confidence: 99%